The importance of Mittelstand firms for regional apprenticeship activity: Lessons for policy - Vera Jahn (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2015)
Politicians frequently emphasize the importance of Mittelstand firms for the economy, thereby particularly referring to their enormous engagement in training apprentices. However, there is yet almost no empirical evidence on the question whether Mittelstand firms are in fact excessively active in training apprentices. This paper contributes to the literature by studying whether the relative importance of owner-managed SMEs has an effect on firms' apprenticeship activity. Using a cross section of West German NUTS-3-regions, we find a significantly positive relation between the relative importance of Mittelstand firms and apprenticeship activity on the regional level. However, on the national level an increase in the share of Mittelstand firms turns out to be without effect on apprenticeship activity.
Keywords: C21; D23; I21; 330; apprenticeship; Mittelstand firms; owner-management; SMEs; Germany; regional spillovers